PEOPLE'S ONLINE ASPIRATION AND COMPLAINT SERVICE (LAPOR) AT THE MAKASSAR CITY COMMUNICATION AND INFORMATION OFFICE - Febrilia, Rafifah; Yamin, Muh Nur; Sakawati, Herlina; Purna, Zarni Adia (Jurnal Aktor, 2025)
This research aims to determine the implementation of the People's Online Aspiration and Complaints Service (LAPOR) in the Makassar City Communication and Informatics Service andtheinhibitingfactorsinimplementingthePeople'sOnlineAspirationandComplaintsService (LAPOR) in the Makassar City Communication and Informatics Service. This research uses a qualitative approach with descriptive methods. Data collection was carried out by observation, interviews and documentation. Data analysis techniques use data condensation, data presentation and drawing conclusions/verification. The results of this research indicate that the implementation of the People's Online Aspiration and Complaints Service (LAPOR) in the Makassar City Communication and Information Service has not been implemented well. This refers to 5 indicators of complaint management where the only indicators that are good are Justice with the impartial actions of theLAPORmanagementadmininhandlingcomplaintswhiletheindicatorsthatarenotgoodin implementing this LAPOR system are Commitment to resolving complaints and direct socialization of the LAPOR system, Clarity in direct delivery of information about complaint procedures, ease of application of the LAPOR system and quick response in terms of the time period for resolving complaints in accordance with the SOP. The inhibiting factors in implementing the LAPOR system are the lack of human resource competency for each OPD, the absenceofasupervisoryteamthatcontrolsthefollow-uptohandlingcomplaintsinthefield,the lack of people who know about the existence of the LAPOR system, technical obstacles to the LAPOR application such as complicated complaint procedures and applications that are sometimes slow or unresponsiveness and lack of authority from DISKOMINFO Makassar City to intervene in complaints at the OPD